Reaction kinetics and kinetics models of alkali activated phosphorus slag - Xie, Fuzhu; Liu, Ze; Zhang, Dawang; Wang, Jixiang; Huang, Tianyong; Wang, Dongmin (Construction & building materials, 2020)
•The hydration reaction kinetics of PS activated by a combination of water glass and sodium hydroxide was studied.•The hydration reaction of alkali activated phosphorus slag (AAPS) was facilitated by higher temperature and lower silicate Modulus (Ms).•The differences in the hydration reaction kinetics of AAPS as varying the Ms and curing temperatures were quantified by the kinetic models.•The rate controlling processes of AAPS have shifted with changes in the Ms and curing temperatures discussed. The kinetics of alkali activation of phosphorus slag (PS) is highly related to silicate modulus of the activator and reaction temperature. In present study, it was probed into the hydration reaction kinetics of PS activated by a combination of water glass and sodium hydroxide. The influence of reaction temperatures (from 25 ℃ to 60 ℃) and the activator silicate modulus (Ms, SiO2/Na2O ratio by mass, from 1 to 2) on the hydration reaction kinetics of AAPS were explored by isothermal calorimetric test. The three kinetic models (the exponential mode, the Knudsen linear dispersion mode and the Jander mode) were selected to extract the correlation parameters and quantitatively analyze the acting mechanism on the hydration reaction kinetics of AAPS. The results showed that the effect of different reaction temperatures and Ms on the hydration reaction kinetics of AAPS were prominent. The exponential method was able to satisfactorily model the hydration reaction kinetics of AAPS pastes. However, higher reaction temperatures and lower Ms were required to abstract the desired kinetic parameters when the Knudsen linear dispersion model was used. With the varied curing temperatures and Ms, the variation trends of the time parameters τ and τo (from the exponential mode and the Knudsen linear dispersion mode, respectively) were in line with those trends that the time to acceleration peak and the ending time of induction stage, respectively. According to the Jander model, the rate controlling processes of AAPS shifted from phase boundary reaction controlling process (the N values less than 1) to diffusion controlling process (the N values more than 1) with decreasing Ms and increasing curing temperatures in the case of higher temperature and lower Ms, respectively. On the contrary, phase boundary reaction controlling process kept unchanged at lower temperature (25 °C) and higher Ms (2). Therefore, the conversion of the rate controlling processes of AAPS was responsible for the differences in the hydration reaction kinetics of AAPS.